Silver nanoparticles with excellent biocompatibility block pseudotyped SARS-CoV-2 in the presence of lung surfactant - Gupta, Govind; Hamawandi, Bejan; Sheward, Daniel J.; Murrell, Ben; Hanke, Leo; McInerney, Gerald; Blosi, Magda; Costa, Anna L.; Toprak, Muhammet S.; Fadeel, Bengt (Frontiers in Bioengineering and Biotechnology, 2022)
Silver (Ag) is known to possess antimicrobial properties which is commonly attributed to soluble Ag ions. Here, we showed that Ag nanoparticles (NPs) potently inhibited SARS-CoV-2 infection using two different pseudovirus neutralization assays. We also evaluated a set of Ag nanoparticles of different sizes with varying surface properties, including polyvinylpyrrolidone (PVP)-coated and poly (ethylene glycol) (PEG)-modified Ag nanoparticles, and found that only the bare (unmodified) nanoparticles were able to prevent virus infection. For comparison, TiO2 nanoparticles failed to intercept the virus. Proteins and lipids may adsorb to nanoparticles forming a so-called bio-corona; however, Ag nanoparticles pre-incubated with pulmonary surfactant retained their ability to block virus infection in the present model. Furthermore, the secondary structure of the spike protein of SARS-CoV-2 was perturbed by the Ag nanoparticles, but not by the ionic control (AgNO3) nor by the TiO2 nanoparticles. Finally, Ag nanoparticles were shown to be non-cytotoxic towards the human lung epithelial cell line BEAS-2B and this was confirmed by using primary human nasal epithelial cells. These results further support that Ag nanoparticles may find use as anti-viral agents.